2019
DOI: 10.1080/0284186x.2019.1653496
|View full text |Cite
|
Sign up to set email alerts
|

The impact of proton LET/RBE modeling and robustness analysis on base-of-skull and pediatric craniopharyngioma proton plans relative to VMAT

Abstract: Purpose: Pediatric craniopharyngioma, adult base-of-skull sarcoma and chordoma cases are all regarded as priority candidates for proton therapy. In this study, a dosimetric comparison between volumetric modulated arc therapy (VMAT) and intensity modulated proton therapy (IMPT) was first performed. We then investigated the impact of physical and biological uncertainties. We assessed whether IMPT plans remained dosimetrically superior when such uncertainty estimates were considered, especially with regards to sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…It has been shown that this assumption affects the range and biological effectiveness of protons in the patient and is therefore linked to a non-negligible amount of uncertainty. 40,41 Not taking into account variable RBE, possible variations in proton range 42 31 would have led to dosimetric differences of about 1% with minor impact on the modelling results.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that this assumption affects the range and biological effectiveness of protons in the patient and is therefore linked to a non-negligible amount of uncertainty. 40,41 Not taking into account variable RBE, possible variations in proton range 42 31 would have led to dosimetric differences of about 1% with minor impact on the modelling results.…”
Section: Discussionmentioning
confidence: 99%
“…When the plan included more than one stage, an average LET d was computed, by calculating for each voxel an average LET value weighted by the dose delivered in each stage. For each patient, we analysed deposited D RBE calculated with cRBE (RBE=1.1) and vRBE parametric model by McNamara [19], assuming α/β=4 Gy in PTV (based on [26], [27]) and α/β=2 Gy for brain, left and right temporal lobe (LTL and RTL, respectively). The choice of α/β ratio was based on the tumor type and data presented in van Leeuwen et al [27].…”
Section: Deposited D Rbe and Dose Constraints For Brain Necrosismentioning
confidence: 99%
“…[13][14][15][16][17][18] Second, the optimization problem was divided into subproblems calculating McNamara RBE, physical dose, and LET separately. The RBE dose was evaluated at the end of treatment planning 19,20 or sequentially in an iterative process, 21 which does not promise problem convergence.…”
Section: Introductionmentioning
confidence: 99%